The potential of Cosmos sulphureus flower extract as a bioherbicide for Cyperus rotundus - Dyah Respatie; Yudono Prapto; Aziz Purwantoro; Y. Andi Trisyono (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Respatie. D. W, Yudono P, Purwantoro A, Trisyono Y.A. 2019. The potential of Cosmos sulphureus flower extract as a bioherbicide for Cyperus rotundus. Biodiversitas 20: 3568-3574. Cosmos (Cosmos sulphureus Cav.) flower is recognized as natural source of bioherbicide compounds for several weeds. The purple nutsedge (Cyperus rotundus L.) is an important weed, and this research was aimed to determine the effects of cosmos flower extract on this weed. Dried cosmos flowers were threshed and extracted using maceration method with 70% alcohol. The experiment was conducted in the greenhouse using a completely randomized design (CRD) with three replications. Purple nutsedge tubers were planted in polybags and treated with cosmos flower extract applicated once to three times with 300 mL polybag-1 at the concentration of 40%. Different levels of inhibitions on purple nutsedge growth were observed at 30 and 60 days after sowing (DAS) due to the presence of gallic acid in the extract. Growth parameters for purple nutsedge were analyzed using Analysis of Variance (ANOVA) and followed by Least Significant Differences (LSD) at ?=0.05. Significant reductions in the number of mother shoots, daughter shoots, and roots, length of mother leaves, length of rhizomes, root, and total leaf area of the purple nutsedge treated with the cosmos flower extract at 30 DAS compared to those in the control. A significant reduction was also observed in foliage dry weight, underground organs dry weight, and total dry weight of purple nutsedge. The three application times yielded maximum inhibition. In addition, these treatments reduced N, P, and  K content, chlorophyll content, and photosynthesis rates at 30 DAS. These results suggest that cosmos flower extract has the potential for controlling purple nutsedge.